Integrasi Islam dan Budaya Lokal dalam Seni Arsitektur Masjid Kuno di Jawa: Sebuah Tinjauan Umum - Ahmad Zainuri (heritage, 2021)
Abstract This article will explain about the integration of Islam and local culture in the architecture of ancient mosques in Java. The architecture of the ancient mosque to this day is still considered to have a deep meaning. The encounter with local culture and Islam, made Islam transformed into a religion that sees the existing reality. Civilization is in the form of a physical stand firmly in its nuances of locality. Mosques are historical relics for Muslims as evidence that Islamic history has succeeded in bringing civilization to a stop in Java. The mosque is a center for da'wah, education and socio-religious activities. So the establishment of the mosque is not a matter of physical considerations, but metaphysical. The method that the author uses is the historical method. This article only looks at an overview of the architecture of ancient mosques in Java. The content of the discussion describes how Islamic architecture in Java, architectural development, integration of Islam and culture in the art of ancient mosque architecture in Java. In conclusion, there is no certain standard in building and establishing mosques in Java. The architectural style of Javanese Islamic mosques has given its own characteristics for Islam in Java.